Combined experimental and DFT investigation on photovoltaic performance of low-cost metal-free organic dye-sensitized solar cells - Kandasamy M.; Suresh S.; Deepan Kumar M.; Murugesan S.; Selvaraj M.; Prem Ananth K.; Kumar N.; Husain A.; Pugazhenthiran N.; Sathishkumar P.; Ansari M.N.M. (Elsevier B.V., 2025)
Metal-free organic dyes, viz. eosin yellow (eosin-Y), fluorescein and curcumin were used as sensitizers in zinc oxide (ZnO) nanoparticles thin film photoanode based dye-sensitized solar cell (DSSC) and also investigated by density functional theory (DFT). UV?vis spectrophotometer was employed to determine absorption feature of dyes in solar spectrum, adsorption tendency towards ZnO photoanode surface, molar-extinction coefficient and desorbed dye molecules from the photoanode surface. The photovoltaic performance of metal-free organic DSSCs employing imidazole based liquid electrolyte and platinum counter electrode was evaluated under standard light exposure of 85 mW/cm2. Among the dyes, eosin-Y DSSC delivered overall energy conversion efficiency (?) of 0.95 % with short-circuit photocurrent density (Jsc) of 2.98 mA cm?2, open-circuit photovoltage (Voc) of 0.54 V and fill factor (FF) of 0.50, which was about 20 % and 40 % higher than that of the energy conversion efficiency of DSSCs sensitized with fluorescein and curcumin dyes, respectively. The better photovoltaic performance exhibited by the eosin-Y DSSC is credited to its high molar extinction coefficient, intense light absorption in the solar spectrum and good adsorption on ZnO thin film photoanode surface. The maximum driving force for dye molecules regeneration and electron injection value of eosin-Y dye attached on the surface of ZnO cluster (eosin-Y + ZnO) resulted in higher Voc. The outcomes of this experimental data are in well agreement with DFT results. ? 2024 Elsevier B.V.